Efficacy of intrapleural instillation of streptokinase with pigtail catheter drainage in the treatment of tuberculous pleural effusion - S., Sandeepa H.; U., Narendra; Gaude, Gajanan S.; Sandeepa, Supriya (International Journal of Advances in Medicine, 2019)
Background: Tuberculosis is the most common cause of exudative lymphocytic pleural effusion in India. The present study was undertaken to evaluate the efficacy of intrapleural instillation of streptokinase with pigtail catheter drainage in the treatment of tuberculous pleural effusion. Methods: Clinical profile, hospital course and outcome of tuberculous pleural effusion patients at the end of six months of anti-tubercular treatment of 50 patients from January 2009 to June 2010 were analyzed. These patients were randomly divided into two groups. One group (n=25) received intrapleural streptokinase via pigtail catheter and the other group (n=25) received intercostal drainage without intrapleural streptokinase instillation. All the patients received standard daily anti TB regimen of 2HERZ/4HR for a total duration of six months. Results: Majority of the patients were above 40 years of age (60%). The male to female ratio was 2.3:1. The major symptoms of the patients were, fever in 44 patients (88%), cough in 42 patients (84%), breathlessness in 33 patients (66%), loss of appetite in 25 patients (50%) and chest pain in 25 patients (50%). Most of the patients had ADA levels between 40-70 IU/L (48%) and only 6% had ADA levels below 40 IU/L. The mean pleural drainage was 2615±126.1 ml in the study group (intrapleural streptokinase) and 1858 ± 93.3 ml in the control group (p <0.0001). Mean duration of intercostal drainage in the study group was 3.76 ± 0.144 days and it was 5.08±0.199 days in the control group (p <0.0001). The mean duration of hospitalization in the study group was 6.60±0.91 days and it was 8.60 ± 0.57 days in the control group (p=0.06). Conclusion: Intrapleural streptokinase instillation is successful in increasing the total drainage of pleural fluid and results in effective drainage of tuberculous pleural effusion. It is also associated with increased amount of pleural fluid drainage, decreased duration of intercostal drainage, decreased length of hospital stay.